2011
DOI: 10.1093/glycob/cwr090
|View full text |Cite
|
Sign up to set email alerts
|

Impaired hippocampal long-term potentiation and failure of learning in  1,4-N-acetylgalactosaminyltransferase gene transgenic mice

Abstract: Gangliosides (sialic acid-containing glycosphingolipids) play important roles in many physiological functions, including synaptic plasticity in the hippocampus, which is considered as a cellular mechanism of learning and memory. In the present study, three types of synaptic plasticity, long-term potentiation (LTP), long-term depression (LTD) and reversal of LTP (depotentiation, DP), in the field excitatory post-synaptic potential in CA1 hippocampal neurons and learning behavior were examined in β1,4-N-acetylga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Therefore, the impairment in spatial learning in this group was clearly not due to increased locomotor activity after cerebral ischemia. In our previous study (23), both attenuation of LTP induction or DP formation in the field EPSP in hippocampal CA1 neurons and impairment of learning in the 4PTT were observed in β1,4-Nacetylgalactosaminyltransferase gene transgenic mice, suggesting that the impairment of learning in the 4PTT might be related to failure of LTP induction or DP formation in hippocampal CA1 neurons. In the present study, a significant decrease in the time needed to take all 4 pellets in the 4PTT with increased number of trials was seen in group T-10 ( Fig.…”
Section: Referencesmentioning
confidence: 81%
See 1 more Smart Citation
“…Therefore, the impairment in spatial learning in this group was clearly not due to increased locomotor activity after cerebral ischemia. In our previous study (23), both attenuation of LTP induction or DP formation in the field EPSP in hippocampal CA1 neurons and impairment of learning in the 4PTT were observed in β1,4-Nacetylgalactosaminyltransferase gene transgenic mice, suggesting that the impairment of learning in the 4PTT might be related to failure of LTP induction or DP formation in hippocampal CA1 neurons. In the present study, a significant decrease in the time needed to take all 4 pellets in the 4PTT with increased number of trials was seen in group T-10 ( Fig.…”
Section: Referencesmentioning
confidence: 81%
“…Because of the poor swimming ability of gerbils, which are desert animals, the use of the Morris water maze test (35) for evaluation of learning behavior in the transient forebrain ischemia model has resulted in wide fluctuations in experimental results for learning behaviors of gerbils after transient forebrain ischemia (14,31,40). Recently, we incorporated features of the radial 8-arm maze (spatial working memory) (21,37,38) and Morris water maze (spatial reference memory) (35) into an apparatus that can be used to test spatial learning in rodents, named the 4-pellet taking test (4PTT) (18,23). In the present study, we investigated the impairment of learning seen in gerbils after a transient cerebral ischemia, focusing on the relations between the degree of neuronal cell death in the CA1 subfields, the change in properties of synaptic transmission or synaptic plasticity in CA1 neurons, and spatial learning behavior in the 4PTT.…”
Section: -Pellet Taking Testmentioning
confidence: 99%
“…The mice in all three groups showed a significant decrease in the time needed to complete the 4PTT with increasing number of trial days (F (7, 87) = 5.9; P < 0.001). Analysis of variance showed that there was a significant main effect of PDMP treatment (F (2, 7) = 19.3, P < 0.0001) and a non-significant interaction of PDMP treatment and trial day (F (14,87) = 0.68, P = 0.79). Post hoc analysis revealed that mice treated with d-PDMP required a longer time for completion of the 4PTT than mice treated with seen in either the home cage or during the 4PTT (data not shown).…”
Section: -Pellets Taking Test (4ptt)mentioning
confidence: 98%
“…We previously studied the effects of GM1 and GQ1b on induction of LTP in CA1 neurons in rat hippocampal slices and showed that LTP is enhanced by bath application of either ganglioside, with GQ1b having a significantly greater effect than GM1 (12). In our recent study (14), we investigated LTP and LTD in the field excitatory post-synaptic potential (EPSP) in CA1 hippocampal neurons and learning behavior in β1,4-N-acetylgalactosaminyltransferase (β1,4 GalNAc-T; GM2/GD2 synthase) gene transgenic (TG) mice (10), which showed a significant decrease in levels of b-pathway gangliosides (GQ1b, GT1b, and GD1b) and a significant increase in lev-5% Tween 80 in saline (vehicle).…”
mentioning
confidence: 96%
“…On the basis of this viewpoint, we began to analyze the levels of gangliosides in the hippocampal gray matter to find a possible cause of Alzheimer's disease, because the gangliosides have been reported to be involved in memory and learning. [4][5][6][7] We attempted to apply the TLC-Blot/ matrix assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry (MS) system for this study. In 1994, we developed a procedure for transferring phospholipids and glycosphingolipids separated on an high performance (HP) TLC-plate to a poly-vinylidene difluoride (PVDF) membrane, 8) and this method was later applied widely to lipid research.…”
Section: Introductionmentioning
confidence: 99%